The Role of Education in Economic Growth and Breaking the Chain of Poverty in Indonesia - Adelia Azzahra; Riska Rahayu; Nina Siti Marlina; Nur Saebah; Wahyu Eko Saputro (Journal of Management, Economic, and Financial, 2024)
This research explores the crucial role of education in improving the quality of human capital and overcoming poverty in Indonesia. Inspired by literature that emphasizes the complex relationship between education, income inequality, and economic growth on factors affecting poverty, including education, health, and internet access. Key findings show that education, especially high, has a significant positive impact on well-being, with every 1% increase in education contributing to a 1% increase in well-being, a 1% significance rate. Policy recommendations are given to governments to increase investment in education, achieve sustainable economic growth, and reduce poverty rates. Although 20% of the state budget has been allocated to education, challenges remain in providing equitable and quality education across the region, affirming that investment in education is an effective strategy to achieve inclusive and sustainable development.